Hyperbranched Polymers with High Transparency and Inherent High Refractive Index for Application in Organic Light‐Emitting Diodes. (5th February 2016) - Wei, Qiang; Pötzsch, Robert; Liu, Xiaoling; Komber, Hartmut; Kiriy, Anton; Voit, Brigitte; Will, Paul‐Anton; Lenk, Simone; Reineke, Sebastian
Abstract : Hyperbranched polyvinylsulfides have been prepared through a facile, metal‐free, radical induced "A2 +B3 " thiol‐yne polymerization of 1, 3, 5‐tris(naphthalylethynyl) benzene and 1, 4‐dithiolbenzene with three different input ratios. The resulting polymers exhibit excellent optical properties like high transparency and very high refractive index (RI) of up to 1.7839, combined with high thermal stability ( T d5% up to 420 °C) and excellent solution processability. These properties make them ideal candidates as high RI polymeric materials (HRIP) in connection with light out‐coupling schemes for organic light‐emitting diodes (OLEDs). A series of hyperbranched HRIPs with varying monomer compositions have been compared in their optical properties. Finally, phosphorescent monochrome OLEDs are fabricated on top of HRIP layers to test the compatibility of HRIPs with state‐of‐the‐art OLEDs. The results show that the HRIPs do not deteriorate the performance of the OLEDs while maintaining external quantum efficiencies of over 20% for phosphorescent red OLEDs. These results open a pathway toward alternative, low‐cost, and scalable out‐coupling concepts through refractive index matching of the OLED materials and the HRIPs presented. Abstract : Hyperbranched polyvinylsulfides with high refractive indices (up to 1.7839) are used as light out‐coupling layer in phosphorescent monochrome OLEDs, allowing external quantum efficiencies >20%. Refractive index matching of polymers and OLED materials opens a pathway toward alternative, low‐cost, and scalable out‐coupling concepts.